Bioseguridad en la atención odontológica a partir de la pandemia COVID-19: un análisis global de las nuevas medidas - Romero Tapia, Percy (2021)
After the outbreak of COVID-19 in the world, during a health crisis, dentistry as a profession with a high level of risk of contamination poses a challenge, for the restructuring of its procedures. In this regard, different approaches to international guidelines have been reviewed with diverse realities and experiences in the field, reaching recommendations for the design and use of optimal personal protective equipment (PPE) in times of scarcity, minimizing the risks of contamination. However, most of these are not supported by dental scientific evidence, while new devices are being developed, minimizing exposure to aerosol-generating procedures (PGA) as physical barriers.